If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-7X + 2) + -6 = -382 Reorder the terms: 8(2 + -7X) + -6 = -382 (2 * 8 + -7X * 8) + -6 = -382 (16 + -56X) + -6 = -382 Reorder the terms: 16 + -6 + -56X = -382 Combine like terms: 16 + -6 = 10 10 + -56X = -382 Solving 10 + -56X = -382 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -56X = -382 + -10 Combine like terms: 10 + -10 = 0 0 + -56X = -382 + -10 -56X = -382 + -10 Combine like terms: -382 + -10 = -392 -56X = -392 Divide each side by '-56'. X = 7 Simplifying X = 7
| (x-4)-(3x+6)= | | f(x)=9+3X-3X^2 | | 36=360x | | 7/8=-n/5 | | 6(4X+-7)+-3=-69 | | (-9/4-8/9)-(5/4-9)=x | | 1(-3X+10)+-1=24 | | 3(x-5)-5(x-3)=x+8-(x-6) | | -5(-6X+6)+6=-234 | | X+4=8-4x | | 12y-7=20y+33 | | k/8=-3/10 | | -7-[(6-2)-(-10-6)]=x | | -17g=17-18g | | -8=4M+4 | | 7x+4-1= | | 4x+7x=-3+x | | 9+9h=-9+8h | | -125Y+5=-245 | | 2-14q+3q=-13q+16 | | -2x-9=2x | | (4/3)(3x^2) | | -7-[(6-2)-(10-6)]=x | | (4/3)(3^2) | | 4/3*3x^2 | | 23x-7-15x+2=22x-7-14x+13 | | 4p+8p-10=2+9p | | 5y-2(-33+6y)=31 | | 2(a^2)-4=68 | | 2t^2-9t-21=0 | | 15/4=30/m | | 5-2(-33+6y)=31 |